Child Sexual Abuse Prevention Program: Reference to the Indonesian Government - Ghaisani Ikramina Aiffah; Wandera Ahmad Religia (Universitas Airlangga, 2020)
Background: Child Sexual Abuse (CSA) was a global problem widespread in many countries. Komisi Perlindungan Anak Indonesia or Indonesian Children Protection Commission (KPAI) recorded as many as 1.880 children become victims of sexual abuse such as rape, fornication, sodomy and paedophilia. The Government of Indonesia become made become efforts both national and international scale, but there is no effective and applicable program that has been implemented. Objective: The purpose of this article was to analyse the programs had been implemented to prevent sexual violence against children. Method: This article was a literature study by examining 38 articles related to the program against child abuse. The researcher was looking for reference sources from the Science Direct, Sage pub and Google Scholar online become. The keywords used were Child Sex Abuse Prevention Program, Parenting Program, Parent Training, Parent Intervention, Maltreatment, Violence, and Violence Prevention. Result: In children, programs that had been implemented include C-SAPE; IGEL; Train the trainer; BST; A program for minorities in Australia; Cool and Safe. For parents, the programs that had been applied include ACT-RSK; Triple-P; RETHINK; The Incredible Years Parents, Teachers, and Children Training Series; PACE; The Making Choices and Strong Families; The African Migrant Parenting; Strengthening Families; 123 Magic; PDEP and FAST. Conclusion: The sexual violence prevention program for children that can be implemented by the Indonesian government was using teaching methods based on school curricula that can be delivered by teachers. For parent, the program that could be implemented by the Indonesian government was using positive parenting methods that focus on preventing sexual violence against children and delivered by expert facilitators.  To reach children and families with different cultural backgrounds, the Indonesian government could adapt sexual violence prevention programs for the Australian minorities and The African Migrant Parenting.